Studi Pola Sebaran Asap Dan Kondisi Parameter Fisis Meteorologi Berbasis Citra Satelit Himawari-8 (Kasus: Kebakaran Hutan di Provinsi Jambi) - Gerson Sinaga; I Made Yuliara; Ni Nyoman Rupiasih; I Ketut Sukarasa; I. G. A. P Adnyna; I. G. A Widagda (Kappa Journal, 2024)
This research has conducted a study of smoke distribution patterns and conditions of meteorological physical parameters based on Himawari-8 satellite imagery (Case: Forest Fires in Jambi Province). Data analysis was carried out in this study using Himawari-8 satellite image data with processed RGB False Color method in SATAID software. Meteorological factors such as hot spots, rainfall, air temperature, wind direction and speed are parameters that can affect the process of forest fires and smoke distribution. The data collected in this research is secondary data. The meteorological data and smoke images from BMKG Jakarta center, Jakarta, then the data is processed and analyzed so that it can interpret the meteorological conditions and smoke patterns in Jambi Province. The smoke images that have been collected are then processed using a laptop with SATAID Software on channels 3, 4, and 6 so that the color of the smoke and the distribution of brownish forest fire smoke can be seen in the form of images. Based on the results of the research, the state of meteorological physical parameters in Jambi Province shows a state of drought, hot spots totaling 30 locations from June 24 to 28, 2022, and low rainfall is one of the factors that trigger the process of forest fires, air temperature with an average of <25 ℃ is classified as a moderate temperature during forest fires. satellite image data and meteorological condition data in 2022, wind direction and speed below 29 kt (knots) are categorized as moderate wind gusts.